The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1986
DOI: 10.1113/jphysiol.1986.sp016204
|View full text |Cite
|
Sign up to set email alerts
|

Electrophysiology and morphology of vasoactive‐intestinal‐peptide‐immunoreactive neurones of the guinea‐pig ileum.

Abstract: Simultaneous intracellular staining and electrophysiological recording techniques have been applied to neurones of guinea-pig myenteric plexus-longitudinal muscle preparations. With micro-electrodes filled with a solution of the fluorescent dye Lucifer Yellow, neurones were first characterized morphologically and electrophysiologically, and subsequently subjected to an indirect immunohistochemical method for the detection of vasoactive intestinal peptide (VIP)-like immunoreactivity. Cross-correlations of morph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 29 publications
(34 reference statements)
2
33
0
Order By: Relevance
“…This is a non-toxic, fluorescent dye which can stain living neural elements without affecting synaptic transmission or the ability of neurons to generate action potentials (Magrassi et al, 1987;Hanani, 1992; Lees, unpublished observations on guinea-pig enteric neurones). The yellowish fluorescent staining of the principal nerve bundles and of the plexus on the trachealis muscle with this agent, was revealed with the same filter set as required for Lucifer Yellow (Lees and Gray, 1982;Katayama et al, 1986;Lees, 1993). If, however, there were doubt as to the presence of neurone somata among or adjacent to adipocytes, it was found useful to use a rhodamine filter set (Zeiss No.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is a non-toxic, fluorescent dye which can stain living neural elements without affecting synaptic transmission or the ability of neurons to generate action potentials (Magrassi et al, 1987;Hanani, 1992; Lees, unpublished observations on guinea-pig enteric neurones). The yellowish fluorescent staining of the principal nerve bundles and of the plexus on the trachealis muscle with this agent, was revealed with the same filter set as required for Lucifer Yellow (Lees and Gray, 1982;Katayama et al, 1986;Lees, 1993). If, however, there were doubt as to the presence of neurone somata among or adjacent to adipocytes, it was found useful to use a rhodamine filter set (Zeiss No.…”
Section: Methodsmentioning
confidence: 99%
“…At the end of an experiment, the preparation was pinned to a sheet of either thin plastic or of Sylgard and immersed in Zamboni fixative solution at 4°C for 15-20 h. The tissue was then cleared in either dimethylsulphoxide (Sigma) or ethanol (Bornstein et al, 1984(Bornstein et al, , 1991Katayama et al, 1986;Lees, 1993) and washed in phosphate buffered saline (PBS; pH 7.1) and mounted on a glass slide in buffered glycerol (pH 8.6). In the case of biocytin-filled cells, the preparations were subsequently subjected to an indirect immunohistochemical technique to reveal the neurone morphology by exposing them to a solution of streptavidin coupled to the fluorescent probe, Texas Red (Sigma) for 20 min; they were washed in PBS and mounted, as above.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A variety of characteristics can be used to identify AH cells; chief among them is the long afterhyperpolarization that follows their action potentials (see Wood, 1994, for reviews). Many AH cells have been demonstrated to have Dogiel type II morphological features (Bornstein et al, 1984;Erde et al, 1985;Katayama et al, 1986;Iyer et al, 1988;Hendriks et al, 1990;Bornstein et al, 1991) with large round or oval cell bodies and several long, tapering processes that run circumferentially out of the ganglion of origin and which give rise to varicose endings in surrounding myenteric ganglia (Bornstein et al,199 I ). A subtype of Dogiel type II neuron, with multiple, short dendritic processes, has also been described (Stach, 1989) and shown to have a different pattern of local projections to other Dogiel type II neurons .…”
mentioning
confidence: 99%
“…About half of the AH neurones in the pig submucous plexus received fast synaptic input. In the guinea-pig small intestine, such inputs have been noted for AH neurones in the myenteric plexus (Iyer et al 1988;Katayama, Pearson & Lees, 1986; but have been reported as very rare (Hirst & McKirdy, 1975) or absent (Surprenant, 1984 (Tamura, 1992). Low incidence of slow EPSPs and IPSPs The rare occurrence of both slow EPSPs and IPSPs in the pig was surprising in view of the prominence of these synaptic potentials in neurones of the guinea-pig submucous plexus (Hirst & McKirdy, 1975;Surprenant, 1984b).…”
Section: Discussionmentioning
confidence: 99%